Advertising and social inclusion: consumer perception and influence on purchase intention - Simões, Elsa (2023)
The objective of this study was to analyse consumers' perception and attitude towards advertising based on inclusive messages. Four dimensions were observed that show the perception of consumers as to the motives underlying these campaigns on the part of brands, the persuasion capacity of these messages and the purchase intention that may result from this process. The study was contextualized in Portugal and focused on the perception of the Dove brand campaign for “Body Love” lotions by male and female respondents in the 18-25, 26-35 and 36-41 age groups.